Electrochemical Detection of Hydrogen Peroxide Based on Ag-Deposited Carbon Nanosphere Composites. Issue 11 (1st November 2022) - Yu, Rong; Liu, Fuxin; He, Nan; Han, Lingling; Liu, Xiuhui
Abstract : Hydrogen peroxide (H2 O2 ) is closely related to our daily life and health, so it is urgent to accurately detect and analyze its content. Herein, a non-enzymatic H2 O2 electrochemical sensor was successfully constructed based on electrodeposited silver nanoparticles (Ag NPs) on carbon nanospheres (CNs). Electrochemical characterization results showed that Ag NPs/CNs/GCE displayed good electrocatalytic performance for H2 O2 . The diffusion coefficient (D) and heterogeneous rate constant (k 0 ) of hydrogen peroxide were calculated separately. In addition, the sensor had a wide linear range of 4.98 × 10 −9 ∼ 7.29 × 10 −3 M and a low detection limit of 1.66 × 10 −9 M. It also presented excellent anti-interference properties in the presence of various substances. The content of hydrogen peroxide was further detected in real samples of makeup remover, milk and disinfectant with satisfactory recovery rates, confirming its application potential in routine detection.